Zero‐Ohm transmission lines for millimetre‐wave circuits in 28 nm digital CMOS. Issue 11 (1st May 2015) - Tretter, G.; Fritsche, D.; Leufker, J.D.; Carta, C.; Ellinger, F.
Abstract : The design, analysis, modelling and measurement of transmission lines with very low characteristic impedance in 28 nm bulk CMOS is presented. The so‐called zero‐Ohm lines are very well suited for power distribution networks and AC shorts in millimetre‐wave circuits because of their accurate modelling up to extremely high frequencies and because they do not require metal–insulator–metal capacitors, which are usually not available in digital CMOS processes. Instead, they rely on simple metal structures, which can optionally be enhanced by integrating MOS capacitors. Applying transmission line theory, the lines can be described with models, which are scalable in length and width. Implemented test structures demonstrate a compact line of 450 μm length, which transforms an open circuit to an impedance close to 0 Ω for frequencies above 1 GHz.